42The primary care atrial fibrillation (PCAF) service: consultant-led anticoagulation assessment clinics in the primary care setting increase the uptake of anticoagulation therapy in AF patients at high-risk of stroke. (October 2014) - Das, M.; Panter, L.; Connor, N.; Mills, J.; Gupta, D.
Abstract : Introduction: AF confers a 5-6% annual risk of stroke, though this can be significantly reduced by appropriate thromboembolic prophylaxis. However, NICE has estimated that 46% of patients that should be anticoagulated are not. This may be in part due to GP and patient concerns over anticoagulation and lack of awareness of recently-released novel oral anticoagulants (NOACs). We present outcomes from an innovative Consultant-led anticoagulation assessment service: the Primary Care AF (PCAF) service. Methods: The PCAF pathway involves 4 phases. Phase 1 : for each enrolled GP practice, the "true" AF register is established by identifying patients with AF not already on the register. Phase 2 : High-risk patients (CHA2 DS2 -VASc score ≥1) who either are not on anticoagulation or are on warfarin but with a sub-optimal TTR are identified. Phase 3 : Identified patients are invited for review by letter, with phone reminders 1 week and 1 day prior. Phase 4 : PCAF clinics are delivered within the patients' GP practice by a Consultant Cardiologist or Stroke Physician. Where appropriate, anticoagulation is prescribed in accordance with NICE/local formulary guidelines. Results: 42 GP practices have been enrolled to date, covering a population of 284, 945 (AF prevalence 2.0%). After clarifying the AF registers ( Phase 1 ), 5426 high-risk patients were identified, of whom 2398 (44.2%) were not on anticoagulation ( Phase 2 ). After case note reviews to exclude patients in whom AF had resolved or there was a contra-indication to anticoagulation, 1169 high-risk patients not on anticoagulation were invited for review ( Phase 3 ). 1014 patients (87%) attended, of whom 761 (75.0%) had AF and eligibility for anticoagulation confirmed ( Phase 4 ). 745 (97.9%) of these patients agreed to commence anticoagulation (43.0% warfarin, 57.0% NOAC). Taking into account all exclusions, the rate of anticoagulation in eligible patients increased from 76.8% (3028 of 3944) to 95.7% (3773 of 3944) following PCAF service intervention. In addition, 261 of 3028 patients on warfarin (8.6%) had a sub-optimal TTR, of whom 211 (80.8%) attended for review. 137 patients (64.9%) were advised to continue with warfarin after a review of compliance and recent INRs; 74 (35.1%) were offered a NOAC, with 67 (90.5%) agreeing to switch. Based on a NNT with warfarin for 1 year to prevent 1 stroke in a mixed primary/secondary prevention group of 25 from NICE/DoH analyses, 29.8 strokes have been prevented in the 745 high-risk patients not previously on anticoagulation. With the addition of patients with a sub-optimal TTR who have now switched to a NOAC, it can be estimated that >30 strokes have been prevented amongst the 42 GP practices. Conclusion: By bridging the primary/secondary care boundary, Consultant-led anticoagulation clinics in GP practices via the PCAF service have proven to be highly effective in identifying AF patients at high risk of stroke, optimising their treatment and preventing strokes.